GSNOR provides plant tolerance to iron toxicity via preventing iron-dependent nitrosative and oxidative cytotoxicity - Baohai Li (Nature Portfolio, 2019)
How plants deal with iron toxicity is still unclear. Here, the authors reveal that S-nitrosoglutathione-reductase (GSNOR) provides tolerance to iron toxicity by preventing iron-dependent nitrosative and oxidative cytotoxicity in Arabidopsis, legumes, and rice.